2017
DOI: 10.2485/jhtb.26.81
|View full text |Cite|
|
Sign up to set email alerts
|

Erosion by an Acidic Soft Drink of Human Molar Teeth Assessed by X-Ray Diffraction Analysis

Abstract: The aim of this study was to show the reaction varieties of human tooth enamel and dentin with a carbonated soft drink, Sprite. After one week exposing into the soft drink, the sliced tooth specimens were examined by macroscopic and microscopic and then carried out the micro X-ray diffraction analysis using a 100 m diameter X-ray beam. The macroscopic and microscopic results showed the wide varieties from the one showing a very slight increase white-spot areas in the enamel to the another showing almost compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Teeth are exposed to many physical and chemical effects that can cause erosion throughout life 1) . Hard tissue loss that occurs in teeth without caries is classifi ed as abrasion, atrision, abfraction, and erosion [2][3][4][5] . Dental erosion is an irreversible loss of tooth surface due to a chemical process without bacterial invasion 6) .…”
Section: Introductionmentioning
confidence: 99%
“…Teeth are exposed to many physical and chemical effects that can cause erosion throughout life 1) . Hard tissue loss that occurs in teeth without caries is classifi ed as abrasion, atrision, abfraction, and erosion [2][3][4][5] . Dental erosion is an irreversible loss of tooth surface due to a chemical process without bacterial invasion 6) .…”
Section: Introductionmentioning
confidence: 99%
“…The soaked teeth were grouped into two; the lightly dissolved one and extremely heavily dissolved one on the basis of the macroscopical and microscopical features after the soaking experiment according to the preceding experiment 11) . Among the twenty human teeth samples examined in this study, two typical samples were explained in this study.…”
Section: Human Tooth Samplesmentioning
confidence: 99%
“…Artificial caries production was performed using the carbonated soft drink Sprite ® (Coca-Cola [Japan] Co. Ltd., Tokyo, Japan), and the durations of control, 1 day, and 7 days were fixed, as suggested by previous studies 1,2) . Twenty human third molar teeth used in this study were extracted for clinical reasons and pooled in purified water.…”
Section: Humantooth Samplesmentioning
confidence: 99%
“…From studies on human tooth enamel caries, it could be inferred that the appearances of native enamel caries and artificial carious lesions are determined by their diversities in original structural and physico-chemical properties 1,2) . Although the enamel crystallites revealed similarities to hydroxyapatite in electron diffraction and X-ray diffraction (XRD), our studies also revealed significant differences between the enamel mineral and pure hydroxyapatite [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%